Potential of Naringin in Reducing Aorta Lesion Atherosclerosis in Hypercholesterolemia: A Systematic Review - Sutandar, Vivi Hendra (Open Access Indonesian Journal of Medical Reviews, 2022)
Hypercholesterolemia is a condition that affects cholesterol levels because of the increase of LDL. Hypercholesterolemia is connected to atherosclerosis disease, which causes the blockage of blood flow. Naringin is a flavonoid primarily found in the citrus family and proved to have various benefits, one of which is antiatherogenic. The article searching was done in PubMed, Wiley Online Library, Cochrane, ProQuest, ScienceDirect, and Google Scholar databases. The final three studies about naringin supplementation in animals models are assessed. Naringin had an antiatherogenic effect and decreased the aorta lesion in atherosclerosis by several different mechanisms.